Microstructural Evolution of Alcufemnti-0.75Si high entropy alloy processed by mechanical alloying and spark plasma sintering - Kim, Minsu; Sharma, Ashutosh; Chae, Myoung Jin; Lee, Hansung; Ahn, Byungmin (Archives of Metallurgy and Materials, 2021)
In this work, we have designed a new high entropy alloy containing lightweight elements, e.g., Al, Fe, Mn, Ti, Cu, si by high energy ball milling and spark plasma sintering. The composition of si was kept at 0.75 at% in this study. The results showed that the produced AlCuFeMnTisi0.75 high entropy alloy was BCC structured. The evolution of BCC1 and BCC2 phases was observed with increasing the milling time up to 60 h. The spark plasma sintering treatment of milled compacts from 650-950°C showed the phase separation of BCC into BCC1 and BCC2. The density and strength of these developed high entropy alloys (95-98%, and 1000 hV) improved with milling time and were maximum at 850°C sintering temperature. The current work demonstrated desirable possibilities of Al-si based high entropy alloys for substitution of traditional cast components at intermediate temperature applications.
Keywords: Cast components; High-energy ball milling; Intermediate temperatures; Milling time; Si-based; Sintering temperatures; High energy ball milling; High entropy alloy; Mechanical alloying; Powder metallurgy; Spark plasma sintering